What really is a pension crisis? A theoretical argument on the link between ageing, productivity, and retirement - Center for Policy Studies, Budapest; Adascalitei, Dragos; Domonkos, Stefan (Budapest, 2015)
"This paper revisits the arguments put forward by policy-makers about the ongoing crisis of public pension systems. Demographic ageing, high contribution rates, present or future fiscal deficits of the social security budgets, and low productivity levels – all these factors have been identified as the roots of pension crises in various countries. We analyze these conceptualizations of the pension crises in the context of Central and Eastern European political economies. We argue that considering demographic ageing or the fiscal condition of the pension budget akin to a crisis is unwarranted. By contrast, we link the notion of a pension crisis to productivity levels, and subsequently evaluate whether an increase in labor productivity can serve as a solution to the financial strain of public PAYG schemes in Central and Eastern Europe. We find that dependence on foreign direct investments might be a significant hindering factor, and conclude that even sizeable increases in productivity levels might fail to resolve the financing difficulties of public PAYG systems in Central and Eastern Europe. Under these circumstances, austerity, especially increases in the retirement age accompanied by policies of active ageing, appear to be the most acceptable solution to the fiscal problems of exiting PAYG pension systems."